Altered DNA repair creates novel Alu/Alu repeat‐mediated deletions. Issue 5 (19th March 2021) - Morales, Maria E.; Kaul, Tiffany; Walker, JaNiece; Everett, Chelsea; White, Travis; Deininger, Prescott
Abstract: Alu elements are the most abundant source of nonallelic homology that influences genetic instability in the human genome. When there is a DNA double‐stranded break, the Alu element's high copy number, moderate length and distance and mismatch between elements uniquely influence recombination processes. We utilize a reporter‐gene assay to show the complex influence of Alu mismatches on Alu‐related repeat‐mediated deletions (RMDs). The Alu/Alu heteroduplex intermediate can result in a nonallelic homologous recombination (HR). Alternatively, the heteroduplex can result in various DNA breaks around the Alu elements caused by competing nucleases. These breaks can undergo Alt‐nonhomologous end joining to cause deletions focused around the Alu elements. Formation of these heteroduplex intermediates is largely RAD52 dependent. Cells with low ERCC1 levels utilize more of these alternatives resolutions, while cells with MSH2 defects tend to have more RMDs with a specific increase in the HR events. Therefore, Alu elements are expected to create different forms of deletions in various cancers depending on a number of these DNA repair defects.